Kinetic Modeling and Biological Activities of Rosa canina L. Pseudo-Fruit Extracts Obtained via Enzyme-Assisted Extraction - Zafeiria Lemoni; Styliani Kalantzi; Theopisti Lymperopoulou; Andromachi Tzani; Georgios Stavropoulos; Anastasia Detsi; Diomi Mamma (Antioxidants)
This study investigates the enzyme-assisted extraction (EAE) of bioactive compounds from the pseudo-fruit of the wild rose (Rosa canina L.), also known as rosehip, using a commercial cellulolytic enzyme preparation, Cellic® CTec3 HS. The effects of extraction time, solid to liquid ratio, and enzyme loading on total phenolic content (TPC) and total flavonoid content (TFC) were evaluated. The highest yields of TPC (168.3 ± 1.1 GAE/g DM) and TFC (72.3 ± 0.8 mg CAE/g DM) were obtained at 360 min, using 1% (v/v) enzyme loading and a 6% (w/v) solid to liquid ratio. Kinetic modeling of the extraction process was performed using first-order, second-order, Peleg’s, and power law models. The power law model best described the extraction dynamics. The obtained extracts were assessed for their biological activities including antioxidant, antimicrobial, anti-aging, and anti-diabetic properties. The extract obtained under optimal extraction conditions exhibited potent tyrosinase inhibition (80%) and moderate to low inhibition of α-glucosidase (15%) and α-amylase (20%) activities. The IC50 for DPPH radical scavenging was 0.44 μL extract/mL while the extract exhibited significant antibacterial activity against Escherichia coli growth (79% inhibition). These findings suggest that the extract, obtained through EAE, has promising biological properties with potential applications in the food, pharmaceutical, and cosmetic industries.